Discursivizando uma episteme acerca do discurso pedagógico sobre o ensino de Literatura na Educação Básica - Mesquita, Diana Pereira Coelho de (2013)
This research proposes a reflection on the discourses that are propagated about the Literature and its teaching in Basic Education. In this sense, the problematization consists of to analyze how the centrifugal and centripetal forces work in the process of construction and dissemination of discourses on literature and its teaching and affect on the theoretical concepts of Enunciative Subjective Instance (IES) in the corpus Pedagogical Enunciative Subjective Instance (IESpg) e Institutional Enunciative Subjective Instance (IESinst), running into the understanding on the interpellation and position taken´s role in the constitution of the literary reader. The corpus is composed by documents Basic Guidelines for Teaching Literature in Elementary Education (2007) and Municipal Curriculum Guidelines for Teaching Literature (2011). The research is based, mainly, in the tripod theory: Michel Pecheux, Mikhail Bakhtin and Michel Foucault and it aims to launch a general epistemological view on the concepts related to the teaching of literature that permeate the practice of many teachers of this area, taking as input analysis of the underlying concepts and of the epistemological affiliations that emerge from the corpus and to reflect on the role of interpellation and of position taken in the students´ constitution in literary readers. The study takes as its premisse that are the traditionalist/conservative conceptions that cross the literature teachers´ practices - reader´s conceptions , literary text, literacy, canon, meaning/sense, authorship, aesthetics, literature and literary reading - that makes them difficult to build a practice which has the goal to challenge students to be constituted as mature literary readers. To confirm the assumption, we conducted a reflection on these concepts, from the analysis of the corpus and considering, mainly, the concept of interpellation, through a discursive analysis device called Generative-Sentidural Device (DGS), which allowed us to understand the operation of centripetal and centrifugal forces that act on the pedagogical discourse about teaching Literature. The results of the study point to the understanding that the teacher should first sign up in a discursive place of formation of the literary reader. In this discursive place, he must understand: the literary reading as a responsible act; that there is a polyphonic referentiality that constitute each student; and that the interpellation and the position taken faced with a literary text are two processes that must be developed/extended with the students.